PERBANDINGAN BIAYA BEKISTING KONVENSIONAL DAN BEKISTING ALUMINIUM (Studi Kasus: Gedung Rusunawa Pakal, Surabaya) - Mia Sekar Ningrum Mia (Jurnal Vokasi Teknik Sipil, 2024)
Project implementation time planning and cost budgeting are important aspects of project construction management. Project success can be measured by the timeliness of implementation and cost efficiency. One of the important components in construction is formwork, which functions as a concrete mold. The research aims examine time and cost efficiency between customary formwork and aluminum formwork in Pakal Surabaya 5-Storey Rusunawa Building project. The results show that although the initial cost of aluminum formwork is higher (Rp4.144.573.844,00) than conventional formwork (Rp3.530.269.038,00. Aluminum formwork also offers advantages in terms of efficiency, ease of installation, and quality of concrete finish. Thus, despite the larger initial investment, aluminum formwork can save time and long-term operational costs. This research provides recommendations to consider the use of aluminum formwork in future construction projects to improve project efficiency and effectiveness.